Expecting the most unexpected - a harlequin baby! A case report and literature analysis - Sundaramoorthy M. Srinivasan (Our Dermatology Online, 2012)
Twenty eight years old primi gave birth to an amazing live baby by vaginal delivery - a Harlequin. The child was born with massive, diamond-shaped scales which limit the child's movements. The term harlequin comes from the baby's facial expression and diamond-shaped pattern of the scales like the 17th century entertainers, harlequins. As the skin cracks at places of movement the protective function of the skin is lost. Till now the prenatal diagnosis was based on biopsy of fetal skin carried out in an advanced stage of pregnancy. The most important indication of fetal cutaneous biopsy is the diagnosis of genodermatosis and hereditary diseases including Harlequin ichthyosis. It is predictable that for Harlequin Ichthyosis the prenatal test based on DNA will replace the fetal biopsy made before tenth week of gestation by chorionic villus sampling, or even before, with non-invasive analysis of the DNA of fetal cells in maternal circulation. Advances in neonatal intensive care along with scaling being made easier by the use of systemic retinoids has led to improved survival and the use of the name "Harlequin baby" to "Harlequin fetus", "World's Largest Baby" or "World's Smallest Baby". The mortality rate for harlequin ichthyosis is high. With neonatal intensive care and the advent of retinoid therapy, some babies have survived the newborn period. They are still at risk of dying from systemic infection. It's the world's most unconquired medical challenge.